When does supportive climate fail to support frontline employees in service recovery? A complexity theory perspective. (June 2022) - Zhang, Mo; Ren, Shengce; Sun, Yang; Geng, Ruoqi
Abstract: This study presents a case-based asymmetric model for the configuration patterns of a supportive climate and frontline employees' (FLEs) attitudes in service recovery based on job demands-resources (JD-R) theory from a complexity theory perspective. The study evaluated FLEs' perceived support, service recovery awareness (SRA) and emotional responses and how these lead to either enhanced or reduced post-recovery satisfaction (PRS). A fuzzy-set qualitative comparative analysis was conducted on dyadic data gathered from 274 matched FLEs and complaining customers in the hospitality industry. The findings reaffirmed the impacts of perceived support, where perceived co-worker support was found to be the core condition in a supportive climate. The findings also provided more evidence of SRA acting as both a challenge and a hindrance in the hospitality industry. Furthermore, the causal configurations demonstrated that emotional responses did not forecast PRS. This study contributes to the service literature and JD-R theory. The practical implications for the hospitality industry and study limitations are also discussed.